Fear of missing out (FoMO) mediate relations between social self-efficacy and life satisfaction - Deniz, Metin; Deniz, Metin (Springer Int Publ Ag, 2021)
The purpose of this study was to examine whether fear of missing out (FoMO) mediate relations between social self-efficacy and life satisfaction among undergraduates. The participants involved 323 undergraduates (female, 66.3%; male, 33.7%). The age of participants ranged between 18 and 32 years (M = 21.52, SD = 2.69). The study data was gathered using the Fear of Missing out Scale, the Social Efficacy and Social Outcome Expectation Scale and the Satisfaction with Life Scale. The research data were analyzed using the structural equation model and bootstrapping method. As a result of the structural equation model, FoMO mediates the relationship between social self-efficacy and life satisfaction. As a result of the bootstrapping analysis, it was seen that all direct and indirect effects are significant. The results, recommendations, and limitations of the study were discussed.
Keywords: Fomo; Social Self-Efficacy; Life Satisfaction; Undergraduates; Turkey